Validation of an abbreviated instrument to assess veterinary client caregiver burden - Spitznagel, Mary Beth (J Vet Intern Med, 2019)
BACKGROUND: Caregiver burden is present in many clients managing illness in a companion animal, but current assessment tools are time‐consuming and lack normative reference values. OBJECTIVES: Statistical reduction of items in a measure of caregiver burden to create an abbreviated version, validation of the abbreviated version, and calculation of reference values. ANIMALS: None. METHODS: This study was conducted using observational methods. Owners of an ill cat or dog were recruited through social media (n = 429). Veterinary clients with an ill (n = 459) or healthy (n = 961) cat or dog were recruited through a general veterinary and an academic hospital with multiple specialties. The study was conducted in 3 stages: (a) reduction of the Zarit Burden Interview (ZBI) adapted for use in pets via factor and item analyses, (b) psychometric validation of the abbreviated instrument, and (c) standardization of the abbreviated (7 items) and full (18 items) measures. RESULTS: A 7‐item measure showed high correlations with the full measure (r = 0.88‐0.93) and good internal consistency (α = .71‐.75) across samples of veterinary clients with an ill cat or dog. This abbreviated measure correlated significantly (P < .001) and positively with stress (r = 0.40‐0.75) and negatively with quality of life (r = −0.32 to −0.56). Reference values derived from clients with a healthy companion animal suggest “normal” burden ranges of 0 to 17 on the full measure and 0 to 8 on the abbreviated version. CONCLUSIONS AND CLINICAL IMPORTANCE: For situations precluding full assessment of client caregiver burden, this brief 7‐item version can be used with good internal consistency and validity. Reference values can help determine if a client's caregiver burden is increased.